2023
DOI: 10.3389/fsurg.2023.1152666
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a blunt retrohepatic vena cava injury using an atriocaval shunt without sternotomy or thoracotomy: a case report

Abstract: Retrohepatic vena cava (RHIVC) injury is often fatal and can be very difficult to manage. Total hepatic vascular isolation, a shunt, or bypass surgery is required for the surgical treatment of RHIVC injury in hemodynamically unstable patients; however, these are not easy procedures. Here, we present a case of RHIVC injury that was successfully treated by atriocaval shunt placement via a transdiaphragmatic incision without sternotomy or thoracotomy. In addition, we review the resuscitation and surgical procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The retroperitoneal cavoatrial shunt involves the insertion of a tube into the right atrium through a venotomy in the infrarenal IVC, which is in contrast to the atriocaval shunt [55]. Choi et al [56] reported a case in which a retrohepatic IVC injury was successfully treated by employing atriocaval shunt placement through a transdiaphragmatic incision without sternotomy or thoracotomy. On the other hand, the retrohepatic vena cava balloon shunt entails the introduction of a dedicated balloon catheter into the retrohepatic IVC through the saphenofemoral junction [57,58].…”
Section: Shunting Maneuversmentioning
confidence: 99%
“…The retroperitoneal cavoatrial shunt involves the insertion of a tube into the right atrium through a venotomy in the infrarenal IVC, which is in contrast to the atriocaval shunt [55]. Choi et al [56] reported a case in which a retrohepatic IVC injury was successfully treated by employing atriocaval shunt placement through a transdiaphragmatic incision without sternotomy or thoracotomy. On the other hand, the retrohepatic vena cava balloon shunt entails the introduction of a dedicated balloon catheter into the retrohepatic IVC through the saphenofemoral junction [57,58].…”
Section: Shunting Maneuversmentioning
confidence: 99%